2017
DOI: 10.1021/acs.inorgchem.7b01334
|View full text |Cite
|
Sign up to set email alerts
|

Computational Screening of Bimetal-Functionalized Zr6O8 MOF Nodes for Methane C–H Bond Activation

Abstract: Zr-based metal-organic frameworks (MOFs) are promising supports for copper-based catalysts able to activate methane. Homo- and heterobimetal-functionalized NU-1000 MOF nodes were selected to computationally screen the effect of ancillary metals for C-H bond activation, allowing us to correlate activation free energies with chemical descriptors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(75 citation statements)
references
References 59 publications
4
69
0
1
Order By: Relevance
“…Two recent studies of computational screening of bimetallic MOFs will highlight this. First, Gagliardi et al 86 screened a series of homo-and heterobimetal-functionalized NU-1000 MOF nodes selected to computationally screen the effect of ancillary metals for C−H bond activation. Correlating activation free energies with various chemical descriptors of the cluster models studied, they showed that transition state C···H (and O···H) bond lengths were reasonable predictors, and that materials combining Cu and Lewis-acidic metals had encouraging properties.…”
Section: Catalytic Activity and Mechanismsmentioning
confidence: 99%
“…Two recent studies of computational screening of bimetallic MOFs will highlight this. First, Gagliardi et al 86 screened a series of homo-and heterobimetal-functionalized NU-1000 MOF nodes selected to computationally screen the effect of ancillary metals for C−H bond activation. Correlating activation free energies with various chemical descriptors of the cluster models studied, they showed that transition state C···H (and O···H) bond lengths were reasonable predictors, and that materials combining Cu and Lewis-acidic metals had encouraging properties.…”
Section: Catalytic Activity and Mechanismsmentioning
confidence: 99%
“…[27] Computational studies have also shown the potentialo fs uch bimetallic MOFs for variousa pplications, such as CÀHb ond activation. [28] Generation of defects and the synergistic effect between the two metals in bimetallic MOFs could lead to enhanced catalytic activity.H ere, we report ao ne-pot method, eliminating the post synthetic process, for the partial substitution of Fe with Co in an amine-functionalized MOF [NH 2 -MIL-88B(Fe)]. [29] The effects of metal substitution on crystallinity,c rystal structure, stability, and catalytic activity were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Though strictly speaking not a materials characterisation method, increasingly sophisticated systems increasingly rely on supporting understanding of characterisation techniques by computational modelling. This is none the least relevant for catalytic reactions, including single‐site catalysts, an area that has undergone a tremendous amount of progress thanks to method development, increased computational power . Computationally assessing catalytic activity by relating it to descriptors instead of calculating the activation energies of elementary reaction steps in heterogeneous catalytic reactions has been significantly relying on screening linear free energy relationships (LFERs), or linear scaling relations .…”
Section: Identification Of Fenx Single Sitesmentioning
confidence: 99%
“…This is none the least relevant for catalytic reactions, including single-site catalysts, an area that has undergone a tremendous amount of progress thanks to method development, increased computational power. [148][149][150][151][152][153][154][155][156][157][158][159][160] Computationally assessing catalytic activity by relating it to descriptors instead of calculating the activation energies of elementary reaction steps in heterogeneous catalytic reactions has been significantly relying on screening linear free energy relationships (LFERs), or linear scaling relations. [161][162][163][164][165][166][167][168][169] However, the direct transposition of LFER on the single-site systems is problematic as the simple models used for bulk metal systems are not satisfactory to describe directional metal-ligand bonds.…”
Section: Advanced Characterisation Of Fen X Single Site (Ssc) Catalystsmentioning
confidence: 99%